1989
DOI: 10.1002/1097-0142(19890515)63:10<2060::aid-cncr2820631031>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on the presentation and course of chronic myelogenous leukemia

Abstract: It is known that cigarette smoking induces leukocytosis and increased genetic instability in normal individuals. Therefore, a retrospective review was conducted of 173 patients with chronic myelogenous leukemia to detect a possible influence of cigarette smoking on initial characteristics at the time of presentation and on the course of this disease. Thirty-nine patients (23%) were smoking 5 cigarettes/d or more at time of diagnosis. Cigarette smoking was significantly related to male sex (P = 0.0005) and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…We read with interest the paper by Herr et al [l], which confirms our own results [2] regarding the earlier occurrence of blast crisis and death in smokers presenting chronic myelocytic leukemia (CML) as compared with nonsmokers and we would like to add some comments regarding the conclusions of these two studies.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…We read with interest the paper by Herr et al [l], which confirms our own results [2] regarding the earlier occurrence of blast crisis and death in smokers presenting chronic myelocytic leukemia (CML) as compared with nonsmokers and we would like to add some comments regarding the conclusions of these two studies.…”
supporting
confidence: 74%
“…There are striking similarities between the effect of smoking on the evolution of CML in our study [2] and its myelostimulatory activity [3] with regard to the intensity of smoking necessary to observe an effect and the persistence of effect after stopping intoxication. One can therefore consider that a causal relationship between the two effects is likely and that tobacco might act as a promoting factor for the blastic crisis by chronically stimulating myelopoiesis and thus increasing the risk of selecting a blastic clone.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Identification of modifiable lifestyle factors that may improve survival is of interest to women diagnosed with breast cancer as well as their caregivers. Smoking has been associated with increased mortality following diagnosis of a variety of cancers, including prostate[2,3], colorectal[4] and vulvar[5] cancers, leukemia[6] and malignant melanoma[7]. Smoking after breast cancer diagnosis has been shown to adversely affect overall survival[8,9], whereas the association with breast cancer specific survival appears equivocal [10,11,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is known for its ability to increase genetic instability and analysis of 173 CML patients showed that smoking correlated highly significantly with both incidence of blast crisis and overall survival. 211 Clonal evolution was observed in a patient both in the advent of and during the blast crisis since specific subclones could be detected before overt lymphoid crisis that was not identical to the clone present during blast crisis. 212 Another study showed that three subsequent blastic transformations in one patient all showed different rearrangements indicating that multiple clones were generated from the CML progenitor cell, suggesting that there is not one exclusive way to clonal evolution in CML.…”
Section: Blast Crisis CMLmentioning
confidence: 99%